Collaborative learning : a means to creative thinking in design - Pun, Siu Kay. (2012)
Employers are increasingly looking for graduates who can think creatively and collaborate effectively to come up with innovative solutions to complex problems. This paper presents a study on applying a pedagogical approach based on collaborative learning to a course for students from different majors. The objective of the course is to develop in students creative thinking skills in solving design problems. The results show the effectiveness of this approach in making team-learning fun for the students who are from different majors. The team projects completed were highly creative and effective and also showed the influence of their own disciplines in the solutions they came up with.